Quantitative Trait Locus Analysis of Leaf Morphology Indicates Conserved Shape Loci in Grapevine - Demmings, Elizabeth M.; Williams, Brigette R.; Lee, Cheng-Ruei; Barba, Paola; Yang, Shanshan; Hwang, Chin-Feng; Reisch, Bruce I.; Chitwood, Daniel H.; Londo, Jason P. (Frontiers in Plant Science, 2019)
Leaf shape in plants plays important roles in water use, canopy structure, and physiological tolerances to abiotic stresses; all important traits for the future development and sustainability of grapevine cultivation. Historically, researchers have used ampelography, the study of leaf shape in grapevines, to differentiate Vitis species and cultivars based on finite leaf attributes. However, ampelographic measurements have limitations and new methods for quantifying shape are now available. We paired an analysis of finite trait attributes with a seventeen-point landmark survey and generalized Procrustes analysis (GPA) to reconstruct grapevine leaves digitally from five interspecific hybrid mapping families. Using the reconstructed leaves, we performed three types of quantitative trait loci (QTL) analyses to determine the genetic architecture that defines leaf shape. In the first analysis, we compared several important ampelographic measurements as finite trait QTL. In the second and third analyses, we identified significant shape variation via principal components analysis (PCA) and using a multivariate least squares interval mapping (MLSIM) approach. In total we identified 271 significant QTL across the three measures of leaf shape and identified specific QTL hotspots in the grape genome which appear to drive major aspects of grapevine leaf shape.